Avian respiratory and immunosuppressive diseases - a fatal attraction - Ideris, Aini (1999)
The avian respiratory system is an efficient system for gaseous exchange but unfortunately, it is also a direct route to many infections. The structure of the lungs is inflexible, and the mucociliary blanket along the respiratory epithetical lining, the first line of defence, is easily damaged in any infection. A well developed immune system is the next line of defence. However, many pathogens can cause damage to the immune system, resulting in immunosuppression, which in turn, will prediscope the host usually to respiratory disease outbreaks. There is definitely a fatal attraction between respiratory and immunosuppressive diseases, leading to severe and/or prolonged problems. They are responsible for high mortality and large economic loses to poultry producers. Advances made in the molecular biology of these pathogens and increased knowledge on the role of the immune system, give new opportunities towards the control of avian diseases, by vaccination. While there is a need for more work to determine the most appropriate way to produce a vaccine for a given disease, genetic engineering will without doubt, play a significant role in vaccine technology. Researchers in UPM are moving towards this new technology besides improving the conventional vaccines.